Acoustics events across Brazil and around the world (2025-2029) - William D'Andrea Fonseca (2025)
This section brings together some of the important events, congresses, and technical meetings related to acoustics, noise, vibrations, audio, signal processing, and related fields, scheduled for the period 2025--2029. For each item, the date, location, and official website address are provided whenever available. The selection was compiled from calendars and announcements by leading associations and societies, such as ICA, I-INCE, ASA, AES, IIAV, EAA, ISMIR and FIA, among others, as well as by national and regional entities, with the aim of offering a broad overview that includes both major international conferences and regionally focused meetings. Events held in Brazil are highlighted with a yellow star. The summary list of events per year is: 2025 • DAS/DAGA 2025 — 51st Annual Meeting on Acoustics — 17–20 March 2025 — Copenhagen, Denmark • AES International Conference on Diversity, Equity, and Inclusion — 3–5 April 2025 — San Diego, USA • ★ 40th International Audiology Meeting (EIA 2025) — 9–12 April 2025 — Recife, Brazil • ★ INAD 2025 — International Noise Awareness Day — 30 April 2025 — Global • NOVEM 2025 — Noise and Vibration Emerging Methods — 6–8 May 2025 — Garmisch-Partenkirchen, Germany • ICA 2025 — 25th International Congress on Acoustics (joint with ASA 188th Meeting) — 18–23 May 2025 — New Orleans, USA • AES Europe 2025 Convention — 22–24 May 2025 — Warsaw, Poland • AIA 2025 — 51st National Conference of the Italian Acoustics Association — 4–6 June 2025 — Treviso, Italy • NOISE-CON 2025 — 9–11 June 2025 — Portland, USA • Forum Acusticum / Euronoise 2025 — 23–26 June 2025 — Málaga, Spain • ICSV31 — 31st International Congress on Sound and Vibration — 6–11 July 2025 — Incheon, South Korea • AES Latin American Convention 2025 — 15–17 August 2025 — Mexico City, Mexico • INTER-NOISE 2025 — 24–27 August 2025 — São Paulo, Brazil • AES 2025 International Conference on Headphone Technology — 27–29 August 2025 — Espoo, Finland • ★ ENCAC 2025 — National Meeting on Comfort in the Built Environment — 1–4 September 2025 — São Carlos, Brazil • AES International Conference on AI and Machine Learning Audio — 8–10 September 2025 — London, UK • Auditorium Acoustics 2025 — 8–10 September 2025 — Bristol, UK • OSA 2025 — 71st Open Seminar on Acoustics — 8–12 September 2025 — Szczyrk, Poland • AAAA 2025 — 11th Congress of the Alps Adria Acoustics Association — 18–19 September 2025 — Varaždin, Croatia • ISMIR 2025 — International Society for Music Information Retrieval — 21–25 September 2025 — Daejeon, South Korea • ACOUSTICS 2025 High Tatras — 37th International Conference — 1–3 October 2025 — Štrbské Pleso, Slovakia • ★ 1st SOBRAC Southern Region Acoustics Forum — 10 October 2025 — Florianópolis, Brazil • Canadian Acoustics Conference 2025 — 15–16 October 2025 — Calgary, Canada • IISA 2025 — India International Symposium on Acoustics — 30 October–1 November 2025 — Gurugram, India • ★ SOBRAC RJ 2025 — SOBRAC Regional Meeting — 9–10 November 2025 — Búzios, Brazil • ★ COBEM 2025 — International Congress of Mechanical Engineering — 9–14 November 2025 — Curitiba, Brazil • Acoustics 2025 — Sounds of the Sunset Coast — 12–14 November 2025 — Joondalup, Australia • Reproduced Sound 2025 — 18–20 November 2025 — Bristol, UK • 19th Argentine Congress on Acoustics — 19–20 November 2025 — Lanús (Buenos Aires), Argentina • ★ VIII SeGAV — Gaúcho Seminar on Acoustics and Vibrations — 28–29 November 2025 — Online • ASA 189th Meeting (joint with ASJ) — 1–5 December 2025 — Honolulu, USA 2026 • AAS 2026 — American Auditory Society Scientific & Technology Meeting — 26–28 February 2026 — Scottsdale, USA • DAGA 2026 — 52nd Annual Conference on Acoustics — 23–26 March 2026 — Dresden, Germany • ★ SOBRAC NE 2026 — SOBRAC Northeast Regional Meeting — 27 March 2026 — Teresina, Brazil • ★ 41st International Audiology Meeting (EIA 2026) — 16–18 April 2026 — São Paulo, Brazil • ★ INAD 2026 — International Noise Awareness Day — 29 April 2026 — Global • BNAM 2026 — Baltic-Nordic Acoustic Meeting — 4–6 May 2026 — Gothenburg, Sweden • ICASSP 2026 — IEEE International Conference on Acoustics, Speech and Signal Processing — 4–8 May 2026 — Barcelona, Spain • ASA 190th Meeting — Acoustical Society of America — 11–15 May 2026 — Philadelphia, USA • AES Europe 2026 Convention — 28–30 May 2026 — Copenhagen, Denmark • BeBeC 2026 — Berlin Beamforming Conference — 1–2 June 2026 — Berlin, Germany • AES 2026 — 3–6 June 2026 — Catania, Italy • AIA 2026 — 52nd National Conference of the Italian Acoustics Association — 10–12 June 2026 — Perugia, Italy • ICBEN 2026 — Congress on Noise as a Public Health Problem — 14–18 June 2026 — Copenhagen, Denmark • ICUA 2026 — International Conference on Underwater Acoustics — 15–18 June 2026 — Glasgow, Scotland • Quiet Drones 2026 — 4th International Symposium on UAV Noise — 29 June–1 July 2026 — Delft, Netherlands • AVARIG 2026 — Audio for VR/AR and Immersive Games — 30 June–3 July 2026 — Paris, France • ICSV32 — 32nd International Congress on Sound and Vibration — 5–10 July 2026 — Istanbul, Türkiye • NOISE-CON 2026 — 9–11 July 2026 — Long Beach, USA • INTER-NOISE 2026 — 9–12 August 2026 — Adelaide, Australia • FIA 2026 — Ibero-American Congress on Acoustics — 12–14 August 2026 (TBD) — Lima, Peru • Forum Acusticum / Euronoise 2026 — 6–12 September 2026 — Graz, Austria • ISMIR 2026 — International Society for Music Information Retrieval — 8–12 November 2026 — Abu Dhabi, UAE • TECNIACÚSTICA 2026 — Spanish Congress of Acoustics & Iberian Congress on Acoustics — 11–13 November 2026 — Granada, Spain • ★ 31st Meeting of the Brazilian Acoustical Society (SOBRAC 2026) — 16–19 November 2026 — Ouro Preto, Brazil • SAPEM 2026 — Symposium on the Acoustics of Poro-Elastic Materials — 16–20 November 2026 — Marne-la-Vallée, France 2027 • DAGA 2027 — 8–11 March 2027 — Darmstadt, Germany • ★ INAD 2027 — 28 April 2027 (estimated) — Global • ICASSP 2027 — 16–21 May 2027 — Toronto, Canada • Forum Acusticum 2027 (joint conference with ASA) — 30 May–4 June 2027 — Brussels, Belgium • ICTCA 2027 — 30 August–2 September 2027 — Santiago de Compostela, Spain • ICSV33 — 2027 (TBD) — TBD • INTER-NOISE 2027 — 2027 (TBD) — TBD • ISMIR 2027 — 2027 (TBD) — Penang, Malaysia 2028 • DAGA 2028 — 20–23 March 2028 — Stuttgart, Germany • ★ INAD 2028 — 26 April 2028 (estimated) — Global • ICASSP 2028 — 28 May–3 June 2028 — Tokyo, Japan • ICA 2028 + Forum Acusticum 2028 (joint conference) — 11–14 September 2028 — Funchal (Madeira), Portugal • BeBeC 2028 — 2028 (TBD) — Berlin, Germany • ICSV34 — 2028 (TBD) — TBD • INTER-NOISE 2028 — 2028 (TBD) — TBD 2029 • ★ INAD 2029 — 25 April 2029 (estimated) — Global • ICASSP 2029 — 22–27 April 2029 — Copenhagen, Denmark • DAGA 2029 / Forum Acusticum 2029 (Joint Conference) — 4–8 June 2029 — Cologne, Germany